Easy-to-fill asymmetric polymeric micro-reservoirs. Issue 68 (5th July 2016) - Contaldi, Vincenzo; Pastore Carbone, Maria Giovanna; Di Maio, Ernesto; Manikas, Anastasios C.; Netti, Paolo Antonio
Abstract : Thermoplastic, asymmetrical, micrometric reservoirs filled with a desired host molecule are achieved by gas foaming and subsequent filling. This method paves the way to a breakthrough in the vibrant micro- and nanoparticle area. Abstract : In this work, we demonstrate the feasibility of micrometric asymmetric reservoirs made of thermoplastic polymers by using the gas foaming method, which has been recently introduced, and consists in forming bubbles in micro- or nano-metric bulk particles as is done with carbonated drinks. As this simplicity anticipates, this represents a breakthrough in the area of micro- and nanoparticles as it responds to the needs of: (i) breaking the symmetry of commonly available systems, (ii) filling the particles with a multitude of host molecules and solutions, (iii) having different shapes, (iv) having a wide range of particle dimensions, (v) having particles made of a wide range of materials. Here we report the achievement of micrometric spherical particles and of micrometric ellipsoidal particles with eccentric holes, filled with crystal violet or with quantum dots as model host molecules. Raman spectroscopy and optical and electron imaging are utilized to verify the effectiveness of the method. This study should open up the use of micro- and nano-metric reservoirs in a multitude of research areas, from biomedicine and pharmacology, to electronics, energy and optics.